Mucositis oral y su relación con la quimioterapia: Revisión tipo Scoping Review (2022)
Introduction: Oral mucositis is one of the most frequent side effects that occurs in patients with chemotherapy treatment, due to an alteration in the dysbiosis which results in immunosuppression that, given to reduce the number of leukocytes, thus generating the proliferation of microorganisms, contributing to the loss of continuity of oral mucosa.